Comparative analysis of the basic infrastructure's development level, by urban-rural typology - Mihai Alexandru Chiṭea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The present paper follows the evolution of the basic infrastructure development, at county level, focusing on the urban-rural typology, on a ten-year period, starting from the premises of its importance to sustainable development at territorial level. The paper turns to usual statistical methods for the analysis of the indicators specific to this domain, derived from official statistical data sources. The working hypothesis was the following: there is a significant disparity between the categories of counties, by urban-rural typology, namely a lower development level in the case of predominantly rural counties, compared to intermediate and predominantly urban ones, a process that imposes a concentration of investment efforts at this level, in order to reduce the current territorial disequilibrium.
Keywords: O18; 330; basic infrastructure; county level; urban-rural typology